(untitled) (Observatorio Económico, 2012)
Since last year we have witnessed the emergence of strong social movements in different regions of the country, which warrant raising questions about our practices of (de)centralization and of political organization at the regional level. How can we make sense of what is happening in the regions? Is it a contingent political matter or a symptom of an unresolved historical process? The issue is not new; our country lacks an agreed-upon development model for its regions. The way Chile has been organized territorially has always been from the center, without regard for the particular features of our regions. Continue reading...